My bondage and my freedom - Douglass, Frederick, 1818-1895 (Penguin classics., 2003)
"An outspoken abolitionist, Frederick Douglass was born into slavery in 1818, and after his escape in 1838, he repeatedly risked his own freedom as an antislavery lecturer, writer, and publisher. My Bondage and My Freedom represents ten years of reflection following his legal emancipation in 1846 and his break with his mentor, William Lloyd Garrison. Upon its initial publication in 1855, this book catapulted Douglass into the international spotlight as the foremost spokesman for American blacks - free and slave. Written during his celebrated career as a speaker and newspaper editor, My Bondage and My Freedom reveals the author of the Narrative of the Life of Frederick Douglass (1845) grown more mature, forceful, analytical, and complex with a deepened commitment to the fight for equal rights and liberties."--Jacket.